(untitled) (Journal of Hama University, 2024)
Multiple sclerosis is a chronic inflammatory disease of central nervous system of autoimmune etiology mediated by activated T cells and have a great impact on the quality of life of patients. comparative studies of different populations have revealed prevalence and incidence rates that vary with geography and ethnicity. optic neuritis it is considered one of the main features in addition to diplopia ,limitation of movements of eye and nystagmus, in our study we noticed the predominance of the female 60% and the percentage of optic neuritis in patients with multiple sclerosis 32.85%. multicenter studies are required to give more accurate results.